EXPRESSIVE ADAPTATION IN LOCALIZATION OF ENGLISH E-COMMERCE APPLICATION’S ACCOUNT PAGE INTO BAHASA INDONESIA - Felicia, Raden Roro Shinta (UG Journal, 2020)
This is a research on how expressive adaptation, the level of expressive adaptation, and the sentence type of expressive adaptation in the localization of e -commerce application’s account page. The method used in this study is qualitative method. This study aims to describe the expressive adaptation, the level of expressive adaptation, and the sentence type of expressive adaptation in the localization of e -commerce application’s account page. The result shows that the expressive adaptation composes 38% of all localization, the level of expressive adaptation is mostly in the level of word, and the sentence type of expressive adaptation is mostly in imperative sentence.